DETERMINATION OF THE USABLE AREA OF THE IMPROVED GRID BAR - Imomnazarova Nurzhakhon Toktaboevna (Web of Journals Publishing, 2025)
In the article the grate, which is the main working part of the process of cotton cleaning at cotton ginning plants, is improved, and also the useful surface of the improved grate is determined using modern computer programs. As a result, a certain reduction of the useful surface of the grate and its mass compared to the existing grate has been achieved.
Keywords: Cotton, fiber, seed, lint, cleaner, calosnik, mesh surface, inlet pipe, outlet pipe, saw gin, roller gin, press, stone catcher.